Smart government initiatives: Transforming global supply chains through digital change - Alzoubi, Haitham M.; Tan, Cheng Ling; El Khatib, Mounir; Alshurideh, Muhammad Turki; Shwedeh, Fanar; Yanamandra, Ramakrishna; Lee, Khai Loon (IRMM, 2025)
This empirical research aims to explore the effects of smart government initiatives on the global supply chain to evaluate the pharmaceutical manufacturing industry in the UAE. Through the synthesis of information collected from this sector’s stakeholders, the research reveals how digital innovation, spurred by smart initiatives initiated by the government, acts as a mediator between supply chain efficiency and effectiveness. The research also shows strategies which encompasses data analytics, IoT and blockchain revolutionise and transform the supply chain by increasing its transparency, responsiveness and flexibility. These digital changes, which have been supported by government policies, not only enhance efficiency, but also help improve coordination between supply chain members and optimize performance indicators internationally. The research findings presented here are relevant to policymakers and leaders of industries to design great technologies for supply chain improvements. Therefore, the study has implications that make it necessary for government agencies to develop effective strategies and policies that support smart causes meant for enhancing digital integration in the sectors. Overall, the study for the pharmaceutical manufacturers indicates that the willingness to adopt digital change supported by governmental frameworks leads to significant improvements of the supply chain performance regarding lead time as well as reliability. In addition, these advancements can contribute toward global competitiveness through the superior management of supply networks especially for global supply chains and reducing risks of supply chain disruptions.